Application of green-emitting ZnS:Eu2+ for boosting the spectrum of white light-emitting diode packages - Nguyen Thi, Dieu An; Dang Huu, Phuc (Institute of Advanced Engineering and Science, 2022)
Through utilizing a nonlinear application to acquire the best lumen efficiency (LE) for radiation (also known as LER) when color rendering index (CRI) value, especially CRI of R9 for strong red exceeds 90 with correlated color temperature (CCT) range of 2700-6500 K, the white light emitting diodes (WLED) package with adjustable CCT value and comprised of mixed-type light-emitting diodes (LEDs) can be acquired. The WLED model here contains blue and red LEDs with direct emission and a phosphorconversion blue LED or pc/B-LED (including orange and green phosphors mixed with blue LED colorant). The peak wavelengths of each LED constituent are 465 and 628 nm for LEDs in blue and red, 452 nm for the blue LED colorant, 530 and 586 nm for the phosphors exhibiting green and orange colors. Under the CCT of 2722-6464 K, the attained actual LED package, either with conversion phosphor, in red or in blue, possibly displays both CRI and R9 values measured from 90 to 96, color quality scale (CQS) values measured from 89 to 94, with LERs and LEs of 303-358 lm/W and 105-119 lm/W, respectively.